Implementasi Sistem Administrasi Digital Kepabeanan dan Cukai di KPPBC TMP C Ketapang - Maulana, Ferdi; Ruhibnur , Refid; Darmanto, Darmanto (Pengelola Jurnal Politeknik Negeri Ketapang, 2024)
This study aims to implement the Digital Customs and Excise Administration System at the Customs Counseling, Service, and Consultation Office (KPPBC) TMP C Ketapang to enhance the efficiency and effectiveness of administrative services. The system development method used is Agile Software Development with a Scrum model approach, enabling rapid iterations and adaptations based on user needs. The system is designed through four main stages: system architecture design, data flow modeling using Unified Modeling Language (UML), database design, and user interface design. The research findings indicate that the system generates various digital forms, such as login forms, staff data entry forms, letter submission forms, and document tracking forms, facilitating structured data management and document tracking. The implementation of this system has successfully improved administrative efficiency, reduced manual errors, and simplified access for service users. The conclusion of this study is that a web-based digital administration system can be an effective solution for digitizing customs services, with recommendations for further development to align with technological advancements and user requirements.